(untitled) (Bangladesh Journal of Endosurgery, 2013)
Purpose: Laparoscopy is gaining popularity over laparotomy in various surgical conditions. Nowadays, an increasing number of diagnostic and therapeutic surgical procedures are being done laparoscopically. The aim of this study is to assess the safety and feasibility of laparoscopy in children. Materials and Methods: This retrospective study was carried out in the Department of Pediatric Surgery of Dhaka Medical College Hospital over a period of 3 years from June 2009 to May 2012. A total of 92 patients were operated laparoscopically up to 12 years of age for different surgical conditions. Data was collected from the hospital records and analyzed retrospectively. Results: Out of 92 laparoscopically performed cases, inguinal hernia repair was done in 30 patients, followed by appendectomy (26), orchiopexy (13), cholecystectomy (11), adnexal mass (05), ambiguous genitalia (04) diagnostic laparoscopy for biliary atresia (02) and for pancreatic pseudocyst (01). Sixty-two were male and age ranged from 2 months to 12 years (mean 7.15 ± 3.35 years). Overall 7.60% patients had some complications. Mean postoperative hospital stay was 2.55 ± 1.37 days. Conclusion: With the recent development of surgical techniques and equipments, laparoscopic surgical procedures are becoming popular day by day and can be performed safely for both diagnostic and therapeutic purposes in children. DOI: http://dx.doi.org/10.11593/bje.2013.0101.0006 Bangladesh Journal of Endosurgery Vol.1(1) January 2013: 21-25